THE EFFECT OF SOAKING TIME AND CONCENTRATION OF SODIUM METABISULFITE ON VITAMIN C LEVELS IN CANDIED MANALAGI MANGO (Mangifera indica L.) - Devianti, Vika Ayu (Indonesian Journal of Pure and Applied Chemistry, 2025)
Mango is a plant that is commonly cultivated and consumed in Indonesia. Mangoes are generally consumed directly, and some are made into processed products, one of which is wet candied. This processing aims to extend the shelf life of the fruit. The process of making wet candied is generally soaked with sodium metabisulfite as a preservative. This study aims to determine the effect of soaking time and sodium metabisulfite concentration on vitamin C levels in Manalagi candied mangoes. Vitamin C is an unstable compound and is easily oxidised during processing. Vitamin C content in Manalagi Candied mangoes was analysed by Iodometric titration method. The results of this study showed that the levels of vitamin C obtained from candied mangoes soaked in sodium metabisulfite for 30, 60, 90, 120, and 150 minutes were 115.3; 153.22; 184.49; 150.0; and 170.32 mg/L, respectively. The level of Vitamin C in candied manalagi mangoes soaked in 50; 100; 150; and 200 ppm sodium metabisulfite was 128; 136.8; 107.84; 123.68 mg/L, respectively. The results of the ANOVA statistical analysis have a Sig value more than 0,05 indicating that the soaking time of sodium metabisulfite and the concentration of sodium metabisulfite have no significant effect on vitamin C levels in Candied Manalagi Mango.